2013
DOI: 10.1186/1477-7827-11-43
|View full text |Cite
|
Sign up to set email alerts
|

Intraovarian regulation of gonadotropin-dependent folliculogenesis depends on notch receptor signaling pathways not involving Delta-like ligand 4 (Dll4)

Abstract: BackgroundIn-situ hybridisation studies demonstrate that Notch receptors and ligands are expressed in granulosa cells (GCs) and in the theca layer vasculature of growing follicles. Notch signaling involves cell-to-cell interaction mediated by transmembrane receptors and ligands. This signaling pathway may represent a novel intraovarian regulator of gonadotropin-dependent follicular development to the preovulatory stage. We hypothesized that blocking Notch pathways would disrupt follicular maturation in the mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Notch signaling pathway with the administration of an inhibitor of the g-secretase complex or DLL4 blocking antibody alters follicular development and induces a disruption of the VEGF-dependent luteal angiogenesis (Garcia-Pascual et al 2013, Jovanovic et al 2013. The present data demonstrate a decrease in progesterone production when CLs obtained from pregnant or superovulated rats were incubated with DAPT, a g-secretase inhibitor.…”
Section: Link Between Notch and Progesterone In CL Functionmentioning
confidence: 53%
See 2 more Smart Citations
“…Notch signaling pathway with the administration of an inhibitor of the g-secretase complex or DLL4 blocking antibody alters follicular development and induces a disruption of the VEGF-dependent luteal angiogenesis (Garcia-Pascual et al 2013, Jovanovic et al 2013. The present data demonstrate a decrease in progesterone production when CLs obtained from pregnant or superovulated rats were incubated with DAPT, a g-secretase inhibitor.…”
Section: Link Between Notch and Progesterone In CL Functionmentioning
confidence: 53%
“…In addition, corpora lutea (CL) from marmosets treated with a neutralizing antibody against DLL4 during the periovulatory period exhibit increased vascular density, but smaller size, with involution of luteal cells, increased cell death, and suppressed plasma progesterone concentrations (Fraser et al 2012). Recently, Jovanovic et al (2013) have demonstrated that the in vivo inhibition of the Notch signaling pathway in mice impairs folliculogenesis and induces the disruption of gonadotropin-stimulated angiogenesis. We have previously demonstrated that Notch1, Notch4 and DLL4 are expressed in small and large luteal cells of CL from pregnant rats and have shown evidences that Notch signaling promotes both luteal cell viability and steroidogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results suggest that Notch is a novel intraovarian regulator that regulates folliculogenesis through vascular and nonvascular mechanisms [29].…”
Section: Discussionmentioning
confidence: 99%
“…In all mammalian species, the proper course of folliculogenesis and oogenesis is the main factor that influences the growth and development of cumulus-oocytes complexes, the maturation of oocytes to reach the MII stage and subsequently monospermic fertilisation (Chaves et al 2012;Songsasen et al 2012;Jovanovic et al 2013;Linke et al 2013;Sobinoff et al 2013). Developing from the preantral into the antral stage, the follicle is finally morphologically modified to three separate populations of somatic cell: theca cells, granulosa cells and cumulus oophorus (Figure 1).…”
Section: Introductionmentioning
confidence: 99%